Islamic fund & wealth management: a way forward - Haron, Razali; Abdullah, Adam (IIUM Press, 2019)
With the overwhelming growth in the global Islamic fund and wealth management sector due to the increasing affluence of Muslim communities wishing to take part in investing surplus funds in Sharīʿah-compliant manner and the existence of non-Muslim wishing to diversify investment via Sharīʿah-compliant funds, more innovative products are being offered. One of them is the Islamic Wealth Management, a relatively new area seen to have great potential to cater to these growing needs. Various measures need to be engineered in order to embark into phases of development and one of them is to increase public awareness. Moving forward, this book comes into existence with a compilation of selected works and researches presented in an international conference, sponsored by the Permodalan Nasional Berhad (PNB) with the theme of Islamic Fund and Wealth Management: A Way Forward. Among the related researches are on sovereign Ṣukūk. The issuance and trading process of Malaysian sovereign Ṣukūk is discussed as well as the structures commonly used in the Ṣukūk issuance to address the current trend of demand for Malaysian sovereign Ṣukūk by foreign investors. Nevertheless, the role of Ṣukūk in financing the state budget deficit in Indonesia is still not significant compared to government bonds due to some challenges. Waqf is also of great interest among the Islamic wealth management community, how Waqf when integrates with element of crowd-funding can become a sustainable source of funding for the development of Waqf lands that have been left idle due to financing constraint. Retirement plan being part of wealth management witnesses the harshness facing remisers due to market downturn and the already bearish market. A voluntary long-term private investment scheme (PRS) has been suggested as a retirement planning for remisiers. Its benefit is discussed in great detail with the hope that the potential of PRS becoming a voluntary long-term investment scheme that supplements retirement savings is enhanced. The book also discusses the optimal level of gold as a reserve asset to be held in portfolios of central banks in order to enhance stability of nations in times of economic, financial and/or geopolitical turmoil given gold’s characteristics as a safe haven asset and a store of value. The nature of gold investment in Malaysia is also discussed, its potentials, operations and the Sharīʿah related issues that can benefit the investors, financial institutions and the policy-makers in Malaysia. The performances of both Sharīʿah compliant and non-Sharīʿah compliant stocks are also discussed in order for investors to have good portfolio selection based on either the choices or the religiosity of investors. Many more issues are discussed and dealt with in this compilation. The choice between Sharīʿah compliant and non-Sharīʿah compliant stocks, discussion on the factors that influence people to choose Employment Providence Fund’s (EPF) Simpanan Sharīʿah retirement fund as to assist the practitioners and policy makers in designing more effective strategies to promote Sharīʿah-compliant retirement plan, an examination on the importance of Sharīʿah Governance Framework (SGF) in Government Linked Investment Company (GLIC), the surplus management in Pakistan takaful industry with regards to regulations and practices. There is also discussion on how Islamic trust services can serve as a viable Sharīʿah-compliant option which helps to smooth the process and assure that fair estate distribution can be executed to legal heirs, on the challenges in the current estate planning and current resolutions on solutions of estate planning and how Sharīʿah-compliant models of Islamic trust services based on Hibah Mu’allaqÉh and Trust with Declaration of Hibah (DoH) are proposed in providing a more efficient estate planning and management. The issue of hedging in Malaysia is also put forward where asymmetric hedging model is found to be more effective than a symmetric hedging model and hedging is dynamic and effective in the Malaysian derivative market. The understanding of Islamic crowd-funding as an alternative instrument of financing for cooperatives’ operation and execution of specific projects is also one of the main interests in this compilation and the significant differences between risk and return and how Sharīʿah penny stocks portfolio is considered better in terms of risk adjusted return compared to the conventional portfolio. Sharī‘ah-compliant issues in relation to Islamic wealth management is also discussed using Maqāṣid-based perspective with examples from a case study of Malaysia. There is also a discussion on how consecutive debt-taking behaviour can elevate financial well-being and lifestyle satisfaction of the households. Nevertheless, regular charity-giving is identified as a must in lifestyle for such outcomes to be achieved among the low-income households. Financial education is without doubt proven to have the role in executing these outcomes. This compilation also provides information on debt from Sharīʿah perspective and the issues related to the practicality of the Debt Management Program (DMP), unravels the grey areas which require future focus of researchers and provides information on debt from Sharīʿah perspective and the issues related to the practicality of the DMP. Study on India revealed that political challenge, lack of confidence, awareness, education, lack of demand, and lack of human capital, religious-based terminologies, lack of proper Sharīʿah governance, and absence of marketing strategies have been identified as the key challenges for the success of Sharīʿah mutual funds in India. The debt determinants of Sharīʿah approved firms in Malaysia as well as the effect of industry type in determining the debt level of the firms are also addressed as well. This compilation is without doubt a success with the contributions from selected authors and co-authors on wide range of issues related to Islamic fund and wealth management locally and globally. It is hoped that this compilation be of beneficial tool at hand to those responsible parties in this area in order to enhance further the Islamic Fund and Wealth Management sector especially in Malaysia.